The Investment and Net Interest Margin: Case Study Commercial Banks in Kosovo - Spahija, Fidane (European Journal of Multidisciplinary Studies, 2016)
In Kosovo, but in all developing countries, the foreign investment is the locomotive of the country that considered as the most important economic sectors. In general it can be concluded that most of the investment originates from developed countries and that these investments return to these places. Origin of investments in Kosovo mainly comes from countries such as Austria, Germany, Slovenia, Great Britain, Switzerland, Turkey, the Netherlands, Albania, Serbia, USA, France, Macedonia, Croatia, Cyprus, Norway, Italy, Greece etc. The banking sector in Kosovo has been very attractive to the foreign investors. A total of nine commercial banks, seven are foreign owned. Foreign investments are primarily generated as investments in shares of foreign shareholders from different countries of the world. Investments in securities have increased by the banking sector in 2014. With the change of the interest rate it has also changed net interest margin of the banking sector. Interest on loans and deposits has continued to decline. Especially interest rates on deposits in 2014 have fallen to 1. 1 percent. This linked to the investment bank in securities of our government as the initiator in this area but cannot be denied to the investment of foreign governments. With the decrease of credit interest rate will be the development of sustainable economic growth and boost investment.
Keywords: Commercial banks; Investments; Net interest margin